2017
DOI: 10.1111/ggi.13024
|View full text |Cite
|
Sign up to set email alerts
|

Do sociodemographic, behavioral or health status variables affect longitudinal anthropometric changes in older adults? Population‐based cohort study in Southern Brazil

Abstract: Despite their association with current height, weight and waist circumference, neither behavioral variables nor the presence of chronic diseases influenced the anthropometric changes. Less educated and unmarried men lose weight at a higher rate, showing a higher risk of sarcopenia. Geriatr Gerontol Int 2017; 17: 2074-2082.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Many studies confirmed the role of socioeconomic factors in the determination of healthy ageing (Supplementary Material, Table 3). Interestingly there are studies which exclusively emphasised the role of childhood or early life background of individuals in the determination of healthy life in the old age (Carrillo-Vega et al, 2019; Castro-Costa et al, 2011; Gao et al, 2017; Goes et al, 2017; Grimard et al, 2010; Gu et al, 2011; Jiang et al, 2019; Mejia-Arango & Gutierrez, 2011; Sadeghi et al, 2015; Saenz & Wong, 2016; Sha et al, 2018; Shen & Zeng, 2014; Torres et al, 2018b). These studies accentuate why considering causality effects is relevant in healthy ageing studies as health in old age is an accumulation of multiple factors influenced over time.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies confirmed the role of socioeconomic factors in the determination of healthy ageing (Supplementary Material, Table 3). Interestingly there are studies which exclusively emphasised the role of childhood or early life background of individuals in the determination of healthy life in the old age (Carrillo-Vega et al, 2019; Castro-Costa et al, 2011; Gao et al, 2017; Goes et al, 2017; Grimard et al, 2010; Gu et al, 2011; Jiang et al, 2019; Mejia-Arango & Gutierrez, 2011; Sadeghi et al, 2015; Saenz & Wong, 2016; Sha et al, 2018; Shen & Zeng, 2014; Torres et al, 2018b). These studies accentuate why considering causality effects is relevant in healthy ageing studies as health in old age is an accumulation of multiple factors influenced over time.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies associated nutritional risk and marital status, but other studies observed some association with weight loss and sarcopenia. Alexandre et al ( 40 ) described an association between absence of marital life and sarcopenia to older adults who participated of the Health, Well-being, and Aging study in 2010 (SABE study), while Góes et al ( 41 ) related that unmarried men lose weight at a higher rate, showing a higher risk of sarcopenia for older adults living in Southern Brazil (EpiFloripa Study).…”
Section: Discussionmentioning
confidence: 99%